Share capital in a limited liability company – an effective form of creditor protection? - Kotowicz, Mateusz (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2014)
This article deals with a draft bill amending the Code of Commercial Companies and the ongoing debate on the planned amendment which includes a proposal to remove a fixed minimum of share capital in limited liability companies. The most important issue under consideration in this paper is the protection of a company’s creditors. The author of the following article, referring to a number of already published statements concerning the draft bill, summarizes the ongoing discussion about the role and the functions of share capital and the proposed new instruments for strengthening creditors’ protection.